Effect of α-tocopherol on antitubercular drugs induced hepatotoxicity - Nehra, Rajiv; Vishwakarma, Pinki; Nehra, Manju; Tyagi, Shashank (International Journal of Research in Medical Sciences, 2016)
Background: Mycobacterium, the causative organism of tuberculosis, is notorious for its ability to develop resistance with monotherapy. To prevent emergence of resistance, combination of antitubercular drugs is given for months to years that can lead to side effects. Hepatotoxicity is one of the commonest side-effect with antitubercular drugs. This study was aimed to explore the hepatoprotective potential of α-tocopherol against experimentally induced hepatotoxicity in albino rabbits. Methods: This experimental study was carried out on 30 rabbits of either sex. They were divided into three groups comprising 10 animals each. Hepatotoxicity is induced experimentally in rabbits following a standard protocol. Group I received normal saline (10 ml/kg bw). Rabbits in group II were treated with first line antitubercular drugs isoniazid (5 mg/kg bw), rifampicin (20 mg/kg bw) and pyrazinamide (25 mg/kg bw) concurrently. Group III received α-tocopherol 200 mg/kg bw along with group II drugs. All drugs were administered by oral route for 90 days. On last day of experiment blood samples were taken to investigate the plasma levels of alanine aminotransferase (ALT), alkaline phosphatase (ALP) and serum total bilirubin. Results: Serum levels of ALT were found to be markedly elevated upon oral administration of antitubercular drugs for 90 days. A statistically significant reduction in ALT levels was noticed when α-Tocopherol was given in doses of 200mg/kg bw along with antitubercular drugs for same duration. Similar results were obtained with serum ALP & serum total bilirubin. Conclusions: α-tocopherol (200 mg/kg bw, oral) was found to have hepatoprotective effect against antitubercular drugs induced hepatotoxicity in albino rabbits.